Calculating the redistributive impact of pension systems in LAC - Alvaro Altamirano; María Laura Oliveri; Mariano Bosch; Waldo Tapia Troncoso (Inter-American Development Bank (IDB), 2023)
This paper examines the implicit subsidies within pension systems across Latin America and the Caribbean (LAC) region. We first calculate the theoretical benefits of pension for hypothetical workers in 25 countries in LAC. We show that, on average, LAC's pension systems are subsidized, as they provide pensions above what workers would have obtained by investing pension contributions in a safe asset. Similarly, pension systems are designed to be progressive by offering higher replacement rates (pensions relative to earnings) for low-income workers. Despite this progressivity, in some countries, absolute subsidies could be higher for high-income workers. This occurs because the cost of one percentage point of the replacement increases with the average pension. Second, using data from social protection surveys, we estimate the incidence of pension systems in five LAC countries. We show that, on average, all five systems provide important subsidies to those workers who obtain a pension. However, given the high levels of informal work, in some countries, those subsidies are highly concentrated among high-income workers. Variation is large across countries. The three highest labor income deciles concentrate 70-95% of all subsidies in defined benefit systems such as Paraguay and Colombia. In defined contribution systems, subsidies are much more progressive, but still, because low-income workers do not qualify for minimum pensions, between 50-60% of subsidies concentrate in the high-income deciles. Countries like Chile, with explicit subsidies targeted at the bottom of the income distribution, obtain a more progressive distribution of subsidies. Because of relatively low participation rates, women have a weaker link with the pension system. They are also less likely to benefit from implicit subsidies. Finally, we show that non-contributory pensions, if well-targeted, largely improve the redistributive properties of pension systems in LAC.
Keywords: H55; J11; J14; J18; J26; J32; 330; Pensions; Subsidies; Taxes; Latin America